Socio-technical transitions and sustainable agriculture in Latin America and the Caribbean: a systematic review of the literature 2010–2021 - Durán, Yuri; Gómez-Valenzuela, Víctor; Ramírez, Katerin (Frontiers in Sustainable Food Systems, 2023)
The challenges and opportunities Latin American and Caribbean countries face to meet sustainable development force nations to seek technological alternatives to ensure better policy design. It also includes technology transfer for the productive inclusion of the rural population in the region. This paper aims to characterize the conceptual frameworks applied to studying socio-technical transitions related to sustainable agriculture in the region. A systematic literature review (SRL) was conducted covering 2010 and 2021. The main findings suggest that the general ideas of socio-technical transition have been used to study sustainable agriculture in LAC. However, its use has been more implicit than explicit, with some predominance of the Strategic Niche Management (SNM) and the Transition Management Approach (TMA) frameworks. In addition, the socio-technical transitions as a straightforward approach have started to be incorporated more clearly after 2020. Finally, the leading technologies to foster socio-technical transitions to sustainable agriculture in the region are related to pest control and soil conservation, so social practices such as certifications have had preponderance in this transition. This paper contributes to the existing literature, broadens the frontier of socio-technical analysis in the transition to sustainable agriculture, and expands our knowledge on applying socio-technical analysis in marginal contexts.